2018
DOI: 10.3892/ol.2018.8716
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between inflammatory tumor microenvironment and cancer stem cells (Review)

Abstract: Cancer stem cells (CSCs), which have a close connection with tumor microenvironment, play a pivotal role in tumorigenesis, tumor progression, and metastasis. The inflammatory microenvironment is an essential component of tumor microenvironment. In the recent years, many studies have demonstrated that the inflammatory microenvironment induces the initiation of tumors, and contributes to the process of the progression of tumors, as well as metastasis. In this review, we summarize the relationship between CSCs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 93 publications
0
53
0
1
Order By: Relevance
“…Tumor microenvironment is usually characterized by an abnormal release of proinflammatory cytokines, which plays an important role in cancer metastasis [17]. Of the important cytokines involved in this process, interleukin 6 (IL -6) have been linked with induction of drug resistance, stem cell like characteristics and EMT induced metastasis in breast cancer [18] [19] [20]. Interestingly, few number of breast cancer studies have suggested that YBX-1 interacts with IL-6 creating a positive feed-forward loop driving EMT-like metastatic properties during cancer progression [21].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor microenvironment is usually characterized by an abnormal release of proinflammatory cytokines, which plays an important role in cancer metastasis [17]. Of the important cytokines involved in this process, interleukin 6 (IL -6) have been linked with induction of drug resistance, stem cell like characteristics and EMT induced metastasis in breast cancer [18] [19] [20]. Interestingly, few number of breast cancer studies have suggested that YBX-1 interacts with IL-6 creating a positive feed-forward loop driving EMT-like metastatic properties during cancer progression [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [117,118] suggest that JNK signaling also plays a role in forming the CSC niche and regulating crosstalk within the niche. JNK signaling also regulates the CSC niche through inflammatory cells, which play central roles in initiation, proliferation, and metastasis of tumors [119].…”
Section: Crosstalk Between the Tumor Microenvironment And Cancer Stemmentioning
confidence: 99%
“…Oral Cancers include many squamous cell carcinomas that may have varying responsiveness to chemotherapy and radiation treatments [1,2]. Recent evidence has demonstrated that a sub-population of oral cancers may be cancer stem cells (CSC), which exhibit cancerous but also stem cell phenotypesincluding chemotherapeutic and radiation resistance [3,4]. Based upon these phenotypes, recent efforts have focused on identifying specific biomarkers to identify tumors with sub-populations of CSC [5,6].…”
Section: Introductionmentioning
confidence: 99%